2018
DOI: 10.1016/j.eml.2018.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Unconventional localization prior to wrinkles and controllable surface patterns of film/substrate bilayers through patterned cavities

Abstract: A novel bilayer is introduced, consisting of a stiff film adhered to a soft substrate with patterned holes beneath the film/substrate interface. To uncover the transition of surface patterns, twodimensional plane strain simulations are performed on the defected bilayer subjected to uniaxial compression. Although the substrate is considered as the linear elastic material, the presence of defects can directly trigger the formation of locally ridged and then folding configurations from flat surface with a relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…This would enable interesting social touch interaction possibilities between a robot and a human by having the robot emulate human-like behavior (e.g. robotic goosebumps to indicate a robot's affective response) [12].…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This would enable interesting social touch interaction possibilities between a robot and a human by having the robot emulate human-like behavior (e.g. robotic goosebumps to indicate a robot's affective response) [12].…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…inCrease builds on the approaches introduced by Guttag and Boyce [7], who proposed PESC designs that consist of flexible materials that are supplemented with relatively hard materials, and by Liao et al [12], who suggested the use of flexible materials that contain cavities. Both approaches are based on the idea of integrating a matrix of either hard material or cavities inside a flexible substrate that allows for changes in surface topography under compression ( Figure 1).…”
Section: Design Approach Of Increasementioning
confidence: 99%
See 1 more Smart Citation
“…For example, Refs. [38][39][40][41] present considerations of wrinkling of stiff films and sheets; the work of Long et al 42 formulate adhesively contact mechanics of large deformation in substrate-supported sheets and Refs. [43][44][45] analyze the instabilities and bifurcation events in the presences of substrate materials.…”
Section: Introductionmentioning
confidence: 99%